KNOWLEDGE AND PRACTICE ON SAFE MOTHERHOOD OF MOTHERS GIVING BIRTH AT PUBLIC HEALTH FACILITIES OF NINH BINH PROVINCE IN 2019 (Vietnam Journal of Community Medicine, 2020)
Objective: To assess knowledge and practice on safe motherhood of mothers giving birth at public health facilities of Ninh Binh province in 2019. Subjects: Mothers giving birth at public health facilities in the province. Rearch method: Descriptive cross-sectional survey. Results: The percentage of mothers who understood correctly about safe motherhood was 38,4%; 97,5% of mothers answered that it was necessary to have health check-up before pregnancy; 86,1% of mothers reported necessity to be vaccinated before becoming pregnant; 60,2% of mothers had correct knowledge that antenatal care needs ultrasound check, blood test and urine test; 19,5% of mothers performed antenatal care 3 times or less, 80,5% of mothers performed antenatal care more than 4 times. Conclusion: The rate of mothers with correct and full knowledge of safe motherhood was very low, the rate of those who had at least 4 times of antenatal care during their pregnancy was quite high.
Keywords: Safe motherhood; mother; knowledge; practice